Hellenistic Nysa-Scythopolis I: the German-Israeli Tell Iẓṭabba excavation project : the 2019-2020 seasons - Lichtenberger, Achim (Monograph series of the Institute of Archaeology, Tel Aviv University, 2025)
"Documents the first three campaigns of the German-Israeli Tell Iẓṭabba Excavation Project at Nysa (Scythopolis), a Hellenistic town founded in the 160s BCE. Excavations provide insights into material culture, with discoveries spanning from the Early Bronze Age to the Byzantine period"-- Provided by publisher